Introduction to the Special Section “Critical Theory and Political Economy of the Internet (Nordmedia 2011)” - Fuchs, Christian and Bolin, Göran (tripleC: Communication, Capitalism & Critique. Open Access Journal for a Global Sustainable Information Society, 2012)
This paper is an introduction to tripleC’s special section “Critical Theory and Political Economy of the Internet” that presents papers from a session at the Nordmedia Conference 2011 (August 11-13, 2011, University of Akureyri, Iceland).
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNjkvdm9sMTBpc3MxcHAzMC0zMg